Pengaruh Media Roda Baca Pintar untuk Meningkatkan Kemampuan Membaca Permulaan Usia 4-5 Tahun - Santi Nurbayani; Asep Dudi Suhardini (Jurnal Riset Pendidikan Guru Paud, 2023)
Abstract. The background of this research is that students in group A of PAUD X have problems reading. In fact, children are not yet able, including children who cannot connect between the sound and the shape of the letters that the child sees. This study aims to improve the early reading skills of children aged 4-5 years through the media of smart reading wheels. The research method is a class action method. The average value of the Pracycle is 65.4. The research results in this Pracycle have said that there are 2 BSH students with a BSH percentage of 20%; students are still said to have MB as many as 5 students with an MB percentage of 50%, while students are said to have BB as many as 3 students with a BB percentage of 30%. The process of implementing learning through the smart reading wheel media to improve initial reading skills in group A PAUD X is carried out for three cycles. The conclusion from the results of observing the teacher's learning activities through the smart wheel game can be seen that there was an increase in Cycle I, Cycle II, and Cycle III. In Cycle I obtained an average value of 72.3% with BSH criteria (Developing According to Expectations). Furthermore, in Cycle II, it obtained an average value of 74.8% with BSH criteria (Developing According to Expectations). Then in Cycle III it obtained an average value of 81.3% with BSB criteria (Very Good Development). Abstrak. Penelitian ini dilatar belakangi oleh siswa di kelompok A Paud X yang mengalami masalah dalam membaca. Nyatanya anak-anak belum mampu diantaranya anak belum bisa menghubungkan antara bunyi dan bentuk huruf yang anak lihat, anak belum bisa mengurutkan susunan nama, anak masih ada yang belum bisa menirukan bentuk huruf-huruf abjad. Penelitian ini bertujuan untuk meningkatkan kemampuan membaca permulaan anak usia 4-5 Tahun melalui media roda baca pintar. Metode penelitian adalah metode tindakan kelas. Nilai rata-rata Prasiklus yaitu mencapai 65.4 hasil penelitian pada Prasiklus ini sudah dikatakan BSH sebanyak 2 siswa dengan presentase BSH 20% siswa masih dikatakan MB sebanyak 5 siswa dengan presentase MB 50% sementara siswa dikatakan BB sebanyak 3 siswa dengan presentase BB 30%. Proses pelaksanaan pembelajaran melalui media roda baca pintar untuk meningkatkan kemampuan membaca permulaan di kelompok A PAUD X dilaksanakan selama tiga siklus. Kesimpulan dari hasil observasi aktivitas pembelajaran guru melalui permainan roda pintar dapat terlihat bahwa adanya peningkatan di Siklus I, Siklus II, dan Siklus III. Pada Siklus I memperoleh nilai rata-rata72.3 % dengan kriteria BSH (Berkembang Sesuai Harapan). Pada Siklus II memperoleh nilai rata-rata 74.8 % dengan kriteria BSH (Berkembang Sesuai Harapan). Pada Siklus III memperoleh nilai rata-rata 81.3 % dengan kriteria BSB (Berkembang Sangat Baik).